Albert Watkins in Selma, CA - Watkins, Howard::::::::: (1978)
Albert Watkins at intersection of E. Front and Center Streets, Selma CA; in background Libby, McNeil water tower. Albert's father worked at this plant in early 1920s. Al's father was so abusive that in 1921 Al's mother took him, his brother Jack, and sister Alma and went to the LA area. The family never saw his father again.